Pengaruh Karakteristik Individu dan Karakteristik Pekerjaan terhadap Kinerja Karyawan PT. TUNAS ARTHA GARDATAMA Bali - Alfi Tarviani; Dewiwati Sujadi (Universitas Triatma Mulya, 2024)
The purpose of this research is to assess the impact of individual and job factors on employee performance. This study is being conducted at PT. Tunas Artha Gardatama Bali. In this study, data was gathered by observation, questionnaires, and interviews. The population consists of employees at PT. Tunas Artha Gardatama Bali, with as many as 40 respondents drawn from the overall workforce population. In this study, descriptive statistical analysis, data instrument test, classical assumptions, multiple linear regression, t test, determination, and beta coefficient were utilized as data analysis approaches. According to the study's findings, individual qualities have a favourable and substantial effect on employee performance.Job characteristics have a positive and considerable impact on employee performance; job characteristics and individual characteristics have a 55.4% influence on employee performance, with individual characteristic factors having a more dominating influence. Researchers in this study can advise PT. Tunas Artha Gardatama Bali to provide work that is appropriate for employees' abilities, provide work that can be completed within working hours, always supervise employees at work, so that later employees try to do work in accordance with procedures, and routinely provide training to employees, so that later employees are able to complete work within the specified timeliness.